2022
DOI: 10.1101/2022.12.01.518675
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitatively mapping local quality of super-resolution microscopy by rolling Fourier ring correlation

Abstract: In fluorescence microscopy, computational algorithms have been developed to suppress noise, enhance contrast, and even enable super-resolution (SR). However, the local quality of the images may vary on multiple scales, and these differences can lead to misconceptions, which is especially intractable in emerging deep-learning ones. Current mapping methods fail to finely estimate the local quality, challenging to associate the SR scale content. Here, we develop a rolling Fourier ring correlation (rFRC) framework… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Fig. 3d shows the representative SR reconstruction, corresponding absolute error map, and confidence maps generated by Bayesian DPA-TISR after correction and rolling Fourier ring correlation (rFRC) 32 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 3d shows the representative SR reconstruction, corresponding absolute error map, and confidence maps generated by Bayesian DPA-TISR after correction and rolling Fourier ring correlation (rFRC) 32 .…”
Section: Resultsmentioning
confidence: 99%
“… a , b , Reliability diagrams generated by Bayesian DPA-TISR models before (left panel) and after (right panel) confidence calibration for microtubule (a) and mitochondrion images (b). c , Representative wide-field (WF) images (bottom left corner of the first column), TISR images (top right corner of the first column), absolute error maps (second column), rFRC maps generated with rolling Fourier ring correlation 32 (third column), and confidence map estimated by Bayesian DPA-TISR models (four column) of microtubules and mitochondria. Scale bar: 1μm (c), and 0.5μm (zoom-in regions in c).…”
Section: Extended Data Figuresmentioning
confidence: 99%
“…4(i). Although Dark sectioning cannot significantly improve the resolution on the basis of Confocal (resolution of Dark confocal being 463.831nm, Confocal being 446.679 nm using rFRC 37 ). Dark sectioning can strengthen the in-focus information to provide more information for SACD, so the resolution of SCAD when imaging thick samples like pine young staminate has been significantly improved from 353.314nm to 216.784nm using rFRC with a successfully SACD reconstruction (RSE of Dark SACD being 0.0208, RSE of SACD being 0.0210) under the same parameters.…”
Section: Resultsmentioning
confidence: 99%
“…We use rFRC mapping 37 to analysis the resolution of SOFI/SACD. The rFRC map denotes the spatial distribution of resolution.…”
Section: Rfrc Mappingmentioning
confidence: 99%
“…Fourier ring correlation (FRC) analysis demonstrated that the reconstructed image has a resolution of approximately 69 nm (Figure 4g). 79 Analysis of rolling Fourier ring correlation 80 (rFRC) on reconstructed images reveals varying local resolutions with a median value of 43 nm (Figure S20), potentially attributed to differing focal planes of the inner membrane and pseudopodia, probe signal strength variations, and membrane fluidity affecting localization accuracy in live cells. In brief, SQ-F-based super-resolution imaging of living cell membranes visualized the ultrastructure of pseudopodia.…”
mentioning
confidence: 99%